Ecology as an Independent Science - Askarkhodjaeva Karima Usmandjanovna (International Journal on Orange Technologies, 2020)
This article examines ecology as an independent science. The article describes a brief history of ecology, the basic concepts. The author analyzes the subject, tasks, development trends of ecological science